Transversality of environmental policy in the Amazon: an analysis of the sustainable BR-163 plan from the multiple streams model - Antelo, Fernanda do Socorro Ferreira Senra (Universidade Federal Rural do Rio de Janeiro, 2018)
This paper analyzes the process of elaboration of the Sustainable Regional Development Plan for the Area of Influence of Highway BR-163 (Cuiabá-Santarém). From John W. Kingdon's (2003) Multiple Streams Model, we sought to understand the process of elaborating a public policy that sought to break with the centralizing and authoritarian pattern of execution of major infrastructure works in the Amazon. The methodology used was bibliographical review, documentary analysis and interviews in Belém, Santarém and Brasília with representatives of governmental and non-governmental institutions involved in the construction of this public policy.